Technological advancements in food processing and packaging [Editorial] - Fadiji, Tobi; Pathare, Pankaj B. (MDPI, 2023)
The global challenge of providing sufficient, safe, and sustainable food to a growing population requires continuous food processing and packaging technology advancements. With the world’s population projected to exceed 9 billion by 2050, addressing the increasing demand for food production and agricultural productivity is more critical than ever. To bridge this gap and ensure food security, exploring innovative approaches that enhance the efficiency and effectiveness of food processing and packaging is essential. These advancements not only play a crucial role in maintaining food safety and quality but also contribute to sustainability efforts by reducing food waste, optimizing resource utilisation, and preserving the nutritional value of food. By continually pushing the boundaries of technology and exploring novel techniques, we can meet the challenges of feeding a growing population while safeguarding the environment and ensuring the long-term availability of safe and nutritious food. This Special Issue brings together a collection of research papers highlighting the latest developments and applications in food processing and packaging, aiming to ensure food safety, extend shelf life, and preserve nutritional value. The diverse range of topics covered in this issue demonstrates the multidisciplinary nature of this field and the need for innovative solutions to meet the future demands of the food industry. The issue consists of three sections, focusing on innovative packaging solutions for food quality and safety [1,2,3], enhancing food safety and quality [4,5,6], and mechanical innovations in food processing [7]. As Guest Editors of this Special Issue, we would like to thank the authors for their valuable contributions and the Editorial Staff of Processes for their professional support during the publication process. We believe that this compilation will prove instrumental in enhancing postharvest technology, a pivotal element of ensuring global food security.